The Influence of Religiousness on Resilience in Failure Situations - Kencana, Yerikha Puteri Dewi (Jurnal Indonesia Sosial Sains, 2025)
This research examines the influence of religiosity on resilience in individuals facing failure. Titled "The Influence of Religiosity on Resilience in Situations of Failure," the study aims to understand how different levels of religiosity affect resilience amid the psychological stress of failure. Data was collected from 100 adults aged 18-65 who had experienced failure and were members of a religious community. Participants completed the Brief Resilience Scale (BRS) questionnaire to measure resilience and the Religious Commitment Inventory (RCI) to measure religiosity. The research hypothesis stated that higher levels of religiosity correlated with greater resilience. The results showed that religiosity has a direct impact on resilience in the context of failure. The findings revealed a positive relationship between religiosity and resilience, supporting the hypothesis that the more religious a person is, the higher their resilience. This relationship was significant, with t-tests and F-tests confirming that religiosity contributed significantly to explaining variation in participants' resilience scores. Regression analysis reinforced these findings, emphasizing the importance of religiosity for resilience. Greater commitment to religious practices and beliefs was shown to improve coping strategies, emotion regulation and the ability to bounce back from failure. The findings imply that religiosity can act as a protective factor, providing individuals with a sense of purpose, meaning and community support to cope with adversity and failure. This research contributes to the understanding of the role of religiosity in enhancing psychological resilience.